STRATEGI PENGEMBANGAN DAERAH TERTINGGAL DALAM UPAYA PERCEPATAN PEMBANGUNAN EKONOMI PEDESAAN - Syahza, Almasdi; Suarman, Suarman (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2013)
The implementation of development, especially in coastal areas of Riau Province, has not been able to improve the welfare of the people especially those living in rural areas. The disparity between rural and urban areas caused by bias and distortion of the development which more pro to urban economy. It causes disadvantaged areas that poor and underdeveloped. The strategy of disadvantaged areas development in Regency of Kepulauan Meranti is the development of agriculture sector based on agribusiness, because most of its population are farmers and fishermen. In the effort to spur the development from economic and social aspects in disadvantaged areas, then the program of rural development should prioritize the three main aspects, those are: 1) Improvement of Peoples Economy (Eradicate Poverty); 2) Improving the Quality of Human Resources (Alleviation of Ignorance); 3) Infrastructure Development.